More Culicoides from Iraq (Diptera: Heleidae). - Khalaf, Kamel Toma (Contributions to Entomology = Beiträge zur Entomologie, 1961)
The author describes some Gulicids from Iraq which he obtained by light-trap collections mainly in 1956. There are given new characteristics for the determination of similar species in this group. Nomenclatural Acts badooshensis Khalaf, 1961 (Culicoides), spec. n. bulbostylus Khalaf, 1961 (Culicoides), spec. n. indistinctus Khalaf, 1961 (Culicoides), spec. n. iraqensis Khalaf, 1957 (Culicoides), syn. n. of Culicoides pallidipennis Carter, Ingram & Macfic, 1920 kasimi Khalaf, 1961 (Culicoides), spec. n. lailae Khalaf, 1961 (Culicoides), spec. n. pictus Khalaf, 1961 (Culicoides), spec. n. pseudopallidus Khalaf, 1961 (Culicoides), spec. n.